Students’ regional potential-based project for vocational education in engineering field - Syahril, Syahril; Wulansari, Rizky Ema; Safitri, Dian; Kiong, Tee Tze; Vitalyevna, Sokolova Elizaveta; Samala, Agariadne Dwinggo (Journal of Engineering Researcher and Lecturer, 2025)
This article discusses Students’ Regional Potential-based Project for Vocational Education in Engineering Field as a strategy to strengthen the quality of project-based learning implementation, covering project-based learning, a project task based on potential of student’s region, the seven standard elements on a project task based on potential of student’s region, the stages of the implementation, and its effectiveness. It was driven by the existence of enormous potentials in Indonesia which have not been optimally developed. Most of universities here are located in urban areas, while most of the students come from rural regions. The previous research discloses students’ positive perceptions toward this learning implementation. It helps them develop their soft skills, fosters better engagement with the learning process, and improves their 4C skills (Critical Thinking, Communication, Collaboration, and Creativity). The approach is able to serve as a model for vocational education learning, particularly in the field of engineering. It not only provides students with the opportunity to acquire knowledge, technology, and soft skills, but also contributes to students’ regional development. This article is highly beneficial for learning implementation in Indonesia, particularly in vocational education, as well as a reference for further studies.